Augmenting basic colour terms in english. Issue 1 (27th January 2015) - Mylonas, Dimitris; MacDonald, Lindsay
Abstract: In an unconstrained colour naming experiment conducted over the web, 330 participants named 600 colour samples in English. The 30 most frequent monolexemic colour terms were analyzed with regards to frequency, consensus among genders, response times, consistency of use, denotative volume in the Munsell and OSA colour spaces and inter‐experimental agreement. Each of these measures served for ranking colour term salience; rankings were then combined to give a composite index of basicness. The results support the extension of English inventory from the 11 basic colour terms of Berlin and Kay to 13 terms by the addition of lilac and turquoise. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 32–42, 2016